Personal data managing in archives: a human centered perspective based on the Brazilian General Data Protection Law - Bagatini, José Augusto [UNESP]; Chaves Guimarães, José Augusto [UNESP]; Gonçalves Sant’Ana, Ricardo César [UNESP] (My University, 2021)
After the expansion of the internet, it was necessary to build legal frameworks that deal with the protection of personal data. In Brazil, there is the law n. 13.709, of August 14, 2018. In view of this, we present here, approaches that subsidize archival processes related to data of this nature.
Gestión de datos personales en archivos: una perspectiva centrada en el ser humano basada en la Ley Brasileña de Protección General de Datos
Gerenciamento dos dados pessoais em arquivos Uma perspectiva centrada no indivíduo com base na LGPD
Keywords: data life cycle; ethic; LGPD; personal data; privacy